Socio-Economic Empowerment of Women Groups through the Poverty Reduction Programme of the Lawra Nandom District Assembly - Dimbie, V.H. (University of Ghana, 2013)
The main aim of this study was to find out the extent the intervention put in place by the Lawra/Nandom District Assembly to reduce poverty and empower women groups socially and economically through the implementation of poverty reduction programme has been achieved. The design for the study was descriptive survey design. The study used questionnaire to obtain data from all beneficiary women groups and interviews from officials. In all, 134 respondents and two interviewees were selected through purposive, proportional and simple random sampling techniques. The data were analyzed with both descriptive and inferential statistics such as chi square analysis. Findings of the study indicate that though the poverty reduction programme is bedeviled with some challenges like difficulty in recovering the loans on schedule, it has largely achieved the purpose of reducing poverty among women in the District Assembly. Beneficiaries invested their loans in farming, petty trading, brewery of „pito‟ and rice and shea butter processing. Additionally, 56.7% of the women used the loans to engage in petty trading. Concerning the socio-economic development of the women groups, about 65.7% of the women beneficiaries have seen an improvement in their standard of living such as access to health, education, sanitation, and nutrition. Some of the challenges encountered by the women before obtaining the loan were, writing of proposals, high interest rate, loan payment duration and difficulty in opening new bank accounts. The study concluded that, the intervention put in place by the Lawra/Nandom District Assembly to reduce poverty and to empower women socially and economically has largely been achieved. The study among other things recommended that government should team up with the local rural banks to negotiate for lower interest rate as well as flexible payment terms to encourage more women to acquire more loans for their businesses.
Thesis (MPHIL)-University of Ghana, 2013
Keywords: Women Empowerment; Poverty Reduction; Loans